Generation of continuously tuneable fractional optical orbital angular momentum using internal conical diffraction - LUNNEY, JAMES; RAKOVICH, YURY; EASTHAM, PAUL; DONEGAN, JOHN (My University, 2010)
Abstract: When a left-circularly polarised Gaussian light beam, which has spin angular momentum (SAM) Jsp = ?? = 1? per photon, is incident along one of the optic axes of a slab of biaxial crystal it undergoes internal conical diffraction and propagates as a hollow cone of light in the crystal. The emergent beam is a superposition of equal amplitude zero and first order Bessel like beams. The zero order beam is left-circularly polarised with zero orbital angular momentum (OAM) Jorb = ?? = 0, while the first order beam is right-circularly polarized but carries OAM of Jorb = 1? per photon. Thus, taken together the two beams have zero SAM and Jorb = ?? per photon. In this paper we examine internal conical diffraction of an elliptically polarised beam, which has fractional SAM, and demonstrate an all-optical process for the generation light beams with fractional OAM up to ? 1?
PUBLISHED
Keywords: Optics; Diffraction; Nanoscience & Materials